ANALISA PENERIMAAN DOSEN BARU DENGAN MENGGUNAKAN SAW (SIMPLE ADDITIVE WEIGHTING) - Nutriana Hidayati (Jurusan Teknologi Informasi Universitas Semarang, 2016)
Acceptance of the new lecturer is one of the decision-making process based on selection test of competence through interviews aspect, microteaching and ability to speak English either active or passive in communication. Decisions are taken based on the highest value of the accumulated value calculation selection made in the institution of the Faculty of Information Technology and Communication. SAW (Simple Additive weighting) is a method of ranking the search for a weighted summation of the performance rating for each alternative on all attributes. The calculation of the value of selection acceptance of new lecturers with perangkingan method based on three aspects which have been set, getting the order rengking with the highest value is 32.5 in the applicant 1 (P1) as the first rank, and as a potential new lecturers will be accepted on Faculty of Information Technology and Communication.